Kompetensi Managerial Kepala Sekolah dalam Meningkatkan Kedisiplinan Guru di SMK Al Ghozaly Wonosobo - Saefurrahman Saefurrahman; Z. Sukawi; Robingun Suyud El Syam (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
It is very important for the principal to overcome teacher indiscipline by implementing effective management. This will be the basis for achieving educational goals. This field research is a form of qualitative descriptive taking the object of the principal's managerial competence in improving teacher discipline, located at SMK Al Ghozaly Wonosobo, conducted in March 2025 - June 2025 in semester 2 (two) of the 2024/2025 academic year. The subjects of the study included the principal, the curriculum vice principal, and several educators and education personnel. Data were obtained through interviews, observations, and documentation to then be analyzed descriptively. The results of the research show that the principal of SMK Al Ghozaly Wonosobo has implemented the five main functions of management, careful planning, effective organizing, clear notification, motivating direction, and comprehensive supervision. The principal's technical, human, and conceptual expertise play an important role in supporting the improvement of teacher discipline. The implementation of punishment is more prominent and felt directly compared to rewards, the effectiveness of punishment in encouraging minimal discipline, but not yet optimal for long-term behavioral changes, the relationship between leadership communication and clarity of reward-punishment criteria affects teacher acceptance. This finding leads to the direction of future research to examine more broadly the dominant and effective punishment system to encourage minimal teacher discipline through direct sanctions for the sake of more specific precision of findings.